The evaluation of equipment remote operation and pyroprocessing verification in hot cell - NIU Yongsheng; SUN Lixin; WANG Baozhu; ZHANG Han; FU Haiying; DOU Qiang; ZHOU Wei; QIAN Yuan; LI Qingnuan (He jishu)
BackgroundReprocessing technology is recognized internationally as one of the most promising technologies to realize the closed cycle of nuclear fuel. Shanghai Institute of Applied Physics (SINAP) of Chinese Academy of Sciences (CAS) has been focusing on the development of this technology, as well as the corresponding support systems engineering in the past decade. The hot cell is an important guarantee for the practical application of nuclear fuel reprocessing technology, therefore, a remote operation system suitable for reprocessing post-treatment process equipment is developed so that the pyroprocessing experiments of molten salt can be conducted in hot cell.PurposeThis study aims to evaluate equipment remote operation and pyroprocessing verification in hot cell.MethodsMain focus of this study was the fluoride volatility and vacuum distillation process of molten salt reactor fuel salts, and the remote operation evaluation of hot cell equipments and pyroprocessing verification experiments were carried out using multi-view coordination. The workload of the operation of the fluoride volatility and vacuum distillation process units was analyzed and evaluated, and the operation efficiency was obtained based on the frequency and time spent on the basic movements of the manipulator in pyroprocessing verification experiments. On this basis, experiments were conducted on the uranium fluoride volatility in the LiF-BeF2-ZrF4-UF4 salt, and vacuum distillation process in LiCl-KCl, LiF-NaF-KF molten salts. Then, before and after the fluoride volatility experiments, inductively coupled plasma mass spectrometry (ICP-MS) was used to determine the uranium content in molten salt, and the conversion rate and reaction rate of uranium were calculated. The uranium content in the base solution downstream of adsorption column was analyzed to obtain the recovery rate of uranium product. Finally, the molten salts evaporation was calculated by the residual mass after the vacuum distillation experiments. The evaporated salts were collected through the condensing cover, and the collection rate was calculated.ResultsThe results of reprocessing validation experiments in hot cell show that the workload of feed and discharge in the operation unit is large than 2.0 on the basis of reasonable arrangement of process equipments in hot cell. The load values for the on/off operation are relatively small, with values of 0.07 and 0.14, respectively. In the operations of processes, due to the various types and frequency of the manipulator operation, the feed and discharge units take a long time with a time-consuming of 20 min and 19 min respectively. The operational efficiency of the pyroprocessing in the hot cell can be improved by optimizing processes and reducing unnecessary operations. A uranium conversion rate of 99.8% and recovery rate of over 99% in molten salt are achieved in he uranium fluoride separation experiment. By improving distillation temperature and sealing of components, a higher evaporation rate and a 100% recovery rate of molten salt distillation are achieved in the vacuum distillation experiments.ConclusionsThe designed small-scale fluoride volatility and vacuum distillation devices can be used for remote operation and process experimental research in the hot cell, and the experimental results meet the key process targets. The research work can provide a reference basis for the pyroprocessing of real spent fuel in hot cell.